U-3M plasma startup scenario sustained by gas puffing as a different plasma confinement scenario: first results - Dreval, M.B.; Sorokovoy, E.L.; Mironov, Yu.K.; Pavlichenko, R.O.; Lozin, A.V.; Romanov, V.S.; Pashnev, V.K. (Вопросы атомной науки и техники, 2013)
In order to reduce flux of neutrals into the plasma confinement volume, discharge start-up scenario maintained by impulse gas puffing (GP) has been proposed. Absence of constant working gas feeding in this scenario opens a possibility to reduce working gas pressure in the U-3M vacuum vessel. It was shown that the time of entire vessel filling after sharp gas puffing pulse is about 10…20 ms. In discharges with 5…6 kV on the RF generators and proposed start-up scenario, a delay between GP pulse and plasma creation was shorter than the chamber filling time. The same level of the electron density has been achieved in the discharge under consideration and conventional 5…6 kV discharge maintained by the constant gas feeding only. The Hα emission waveform in the considered discharges is similar to its waveforms in the conventional devices where the sizes of vacuum chamber and plasma are close each other. Для того, чтобы уменьшить поток нейтралов в объем удержания плазмы, был предложен сценарий разряда У-3М, поддерживаемого импульсным напуском газа. Отсутствие постоянной подачи газа в этом сценарии позволяет уменьшить давление рабочего газа в вакуумной камере У-3М. Было показано, что время заполнения вакуумной камеры У-3М после резкого импульса напуска газа составляет около 10...20 мс. В разрядах с 5...6 кВ на ВЧ-генераторах в режиме предложенного сценария напуска газа задержка между импульсом напуска и созданием плазмы была короче времени заполнения камеры. Тот же уровень плотности электронов был достигнут в рассматриваемом разряде и обычном 5...6 кВ разряде, поддерживаемом только постоянной подачей газа. Форма временной зависимости эмиссии линии Hα в рассматриваемых разрядах похожа на форму этой зависимости в обычных установках, в которых размеры плазмы и камеры близки друг к другу. Для того, щоб зменшити потік нейтралів в об’єм утримання плазми, був запропонований сценарій розряду У-3М, що підтримується імпульсним напуском газу. Відсутність постійної подачі газу в цьому сценарії дозволяє зменшити тиск робочого газу у вакуумній камері У-3М. Було показано, що час заповнення вакуумної камери У-3М після різкого імпульсу напуску газу становить близько 10...20 мс. У розрядах з 5...6 кВ на ВЧ-генераторах у режимі запропонованого сценарію напуску газу затримка між імпульсом напуску і створенням плазми була коротшою ніж час заповнення камери. Той же рівень густини електронів був досягнутий в розглянутому розряді і звичайному 5...6 кВ розряді, що підтримується тільки постійною подачею газу. Форма часової залежності емісії лінії Hα в розглянутих розрядах схожа на форму цієї залежності в звичайних установках, в яких розміри плазми і камери близькі один до одного.